The development and application of an antibody microarray as a diagnostic platform for COPD - Selvarajah, Senthooran (2013)
According to the Global Initiative for Chronic Obstructive Lung Disease (GOLD) Management Guidelines (2001), the definition of COPD is “a disease state characterised by airflow limitation that is not fully reversible. The airflow is usually progressive and associated with inflammatory responses of the lungs to noxious particles and gases.” It is becoming an increasing prevalent problem worldwide, with the incidences of morbidity and mortality continually increasing and promoting a lower quality of life in individuals that continue to suffer from it.